Experimental studies on mechanical properties of corroded steel bars after elevated temperature. (2017) - Yan, Xiong; Di, Wu; Yingfeng, Tang; Minqiu, Hu; Hai, Shu
Abstract: The mechanical properties of steel bar deteriorates after erosion and elevated temperature. In the study 16 mm diameter bars were corroded by an electrochemical accelerated corrosion technique, and then heated at temperatures 300, 500 and 700℃. The bars were cooled naturally in furnace to ambient temperature and were tested in tension. The nominal yield strength, nominal ultimate strength and elongation were observed. The observations showed that nominal yield strength, nominal ultimate strength and elongation was changed significantly on the coupling effects of corrosion and temperature.